Law in everyday life and death: a socio‐legal study of chronic disorders of consciousness. (19th February 2014) - Halliday, Simon; Kitzinger, Celia; Kitzinger, Jenny
<x xml:space="preserve">Abstract</x> This paper addresses, from a socio‐legal perspective, the question of the significance of law for the treatment, care and the end‐of‐life decision making for patients with chronic disorders of consciousness. We use the phrase 'chronic disorders of consciousness' as an umbrella term to refer to severely brain‐injured patients in prolonged comas, vegetative or minimally conscious states. Based on an analysis of interviews with family members of patients with chronic disorders of consciousness, we explore the images of law that were drawn upon and invoked by these family members when negotiating the situation of their relatives, including, in some cases, the ending of their lives. By examining 'legal consciousness' in this way (an admittedly confusing term in the context of this study, ) we offer a distinctly sociological contribution to the question of how law matters in this particular domain of social life.